2016
DOI: 10.1016/j.psychres.2016.02.040
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dispositional mindfulness, borderline personality features, and suicidal ideation in a sample of women in residential substance use treatment

Abstract: Borderline personality disorder (BPD), which is characterized by unstable moods, behavior, and relationships, is also associated with heightened suicidal ideation. Prior research has demonstrated that BPD and suicidal ideation are prevalent among women in substance use treatment. Efforts to treat substance use in this population are made difficult due to the severity of BPD, and it is possible that mindfulness-based interventions specific to substance use could be an effective approach for this population. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 61 publications
0
7
0
1
Order By: Relevance
“…2012; Shorey et al, 2016). Moreover, higher levels of trait mindfulness were associated with lower levels of residual depressive symptoms, especially among individuals who have experienced five or more episodes of depression (Radford et al, 2014).…”
Section: Practitioner Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; Shorey et al, 2016). Moreover, higher levels of trait mindfulness were associated with lower levels of residual depressive symptoms, especially among individuals who have experienced five or more episodes of depression (Radford et al, 2014).…”
Section: Practitioner Pointsmentioning
confidence: 99%
“…Mindfulness skills may develop differently in various subgroups of individuals (Liljia, Lundh, Josefsson, & Falkenström, ). Low levels of mindfulness played a significant role in personality psychopathology and were found negatively associated with borderline personality disorder (BPD) features (Fossati, Vigorelli Porro, Maffei, & Borroni, ; Shorey et al ., ). Moreover, higher levels of trait mindfulness were associated with lower levels of residual depressive symptoms, especially among individuals who have experienced five or more episodes of depression (Radford et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Available research indicates that some degree of suicidal ideation is present in 14 per cent of the general population (Kessler et al, 1999) and in approximately 4 out of 10 (38%) psychiatric outpatients (Dhossche, 2000), with risk factors for suicidal ideation having been found to include both personal and clinical characteristics. The presence and severity of suicidal ideation has been found to be associated with: personal characteristics such as gender and ethnicity (Bartels et al, 2008), stressful life events like unemployment (Blakely, Collings, & Atkinson, 2003), marital status (McLaren, Gomez, Gil, & Chesler, 2015) and a comorbid diagnosis of: depressive disorder or bipolar depression (May et al, 2015;Valtonen et al, 2005), anxiety disorder (Machell, Rallis, & Esposito-Smythers, 2016), borderline personality disorder (Shorey, Wolford-Clevenger, Gawrysiak, Anderson, & Stuart, 2016) and/or a substance use disorder (Zhans & Wu, 2014).…”
Section: Death and Suicidal Ideationmentioning
confidence: 99%
“…In a study conducted by Nicastro et al [ 38 ] fewer mindfulness skills were found in BPD patients than in control participants. Findings demonstrate that dispositional mindfulness is negatively associated with BPD features and suicidal thinking among patients in substance use treatment [ 39 ]. The inverse relation between BPD and mindfulness can be explained by the difficulties of BPD patients to be consciously aware of their experiences in the present moment instead of focusing on general concepts.…”
Section: Introductionmentioning
confidence: 99%